(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
This study aims to identify and analyze the efforts of the police in investigating gambling crimes in the city of Makassar and to analyze the factors that influence gambling crime in the city of Makassar. This study uses an empirical method that is supported by field research. Empirical Legal Research is a legal research method that uses Empirical facts taken from human behaviour, both verbal behaviour obtained from human behaviour and verbal behaviour obtained from interviews and real behaviour through direct observation. The results of this study indicate that the implementation of the investigation process on the crime of gambling at the Makassar Police is basically the same as the ordinary criminal investigation but is focused on the arrest of the perpetrator. The process of investigating gambling crimes begins with a police report which is followed up by arrest, detention, search and confiscation to obtain evidence and suspects in accordance with the provisions of article 110 and article 138 of the Criminal Procedure Code and Article 184 KUHAP. The recommendation of this research is that the Police should conduct patrols more frequently by mobilizing every Sector of Police in Makassar City. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis upaya kepolisian dalam penyidikan tindak pidana perjudian dikota Makassar dan untuk menganalisis faktor-faktor yang mempengaruhi tindak pidana perjudian di kota Makassar. Penelitian ini menggunakan metode Empiris yang didukung dengan penelitian lapangan. Penelitian Hukum Empiris adalah suatu metode penelitian hukum yang menggunakan fakta-fakta Empiris yang diambil dari perilaku manusia, baik perilaku verbal yang didapat dari perilaku manusia maupun perilaku verbal yang didapat dari wawancara maupun perilaku nyata yang dilakukan melalui pengamatan langsung. Hasil penelitian ini menunjukkan Pelaksanaan proses Penyidikan terhadap Tindak Pidana Perjudian di Polrestabes Makassar pada dasarnya sama dengan Penyidikan tindak pidana biasa akan tetapi difokuskan pada penangkapan pelaku. Proses Penyidikan tindak pidana Perjudian diawali dengan adanya laporan polisi yang ditindak lanjuti dengan penangkapan, penahanan, penggeledahan, dan penyitaan untuk mendapatkan alat bukti dan tersangka sesuai dengan ketentuan pasal 110 dan pasal 138 KUHAP dan pasal 184 KUHAP. Rekomendasi penelitian ini Kepolisian harus lebih sering melakukan patroli dengan menggerakkan setiap Kepolisian Sektor yang ada di Kota Makassar.